METHODS OF TEACHING AND LEARNING ENGLISH IN SCHOOL AND SOLUTIONS TO PROBLEMS - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi, (Журнал иностранных языков и лингвистики, 2023)
Our article looks at teaching English in schools to a second language learner. It discusses approaches to teaching English.